2009
DOI: 10.1007/s11409-009-9037-5
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive learning strategies: differential development patterns in high school

Abstract: The main objective of this study is to identify the development of students' selfreported use of metacognitive learning strategies during high school. Therefore, the study analyses the differential development patterns of 1,432 students, between grade 10 and 12, in a longitudinal sample. The results suggest that, from a global perspective, there is no development of students' self-reported use of metacognitive learning strategies during high school. The expected gender-specific differences in favour of female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 28 publications
3
35
0
8
Order By: Relevance
“…Research also suggests that the use of MS is linked to age, gender, and socio-economic status (Leutwyler, 2009). The concept was initially associated with Flavell (1971), whose perspective was developmental and very much a product of the then ongoing change in focus in educational psychology from environmental factors to learners themselves and how they interact with information.…”
Section: Metacognitionmentioning
confidence: 99%
“…Research also suggests that the use of MS is linked to age, gender, and socio-economic status (Leutwyler, 2009). The concept was initially associated with Flavell (1971), whose perspective was developmental and very much a product of the then ongoing change in focus in educational psychology from environmental factors to learners themselves and how they interact with information.…”
Section: Metacognitionmentioning
confidence: 99%
“…Both of these studies collected data immediately after the intervention. There was only one longitudinal cohort study that tracked secondary students' meta-cognitive development over a three-year period (Leutwyler 2009). Measured ICU outcomes were limited to increase in cultural knowledge, general awareness of cultural diversity and short-term shifts in attitude.…”
Section: Need For Long-term Interventions Beyond Cultural Awarenessmentioning
confidence: 99%
“…Further studies revealed that developmental patterns of metacognition also differed across gender groups. For instance, girls performed better in strategy knowledge tasks during high school Leutwyler, 2009). But first-grade boys significantly outperformed girls of the same age group in the domain of mathematics within a study conducted by Carr, Jessup, and Fuller (1999).…”
Section: Developmental Aspects Of Strategy Knowledgementioning
confidence: 99%
“…However, there might be further dimensions of strategy knowledge. As Leutwyler (2009) and Phakiti (2008) suggested, the construct of strategy knowledge could show a higher order structure with different factors across domains and facets of the construct. However, in our study, we were did not specify a multidimensional structure as we hypothesized only one latent trait in a single domain.…”
Section: Assessment Of Strategy Knowledgementioning
confidence: 99%